PENGARUH KONSENTRASI SURFAKTAN DAN KECEPATAN PUTAR PENGADUK TERHADAP PROSES PEMISAHAN BITUMEN DARI ASBUTON - Nora Amelia Novitrie; Susianto; Ali Altway (Journal of Research and Technology, 2016)
Asbuton is a rock contain of the bitumen. Asbuton can be used as road construction alternatives after extracting bitumen from the mineral. A method for separating bitumen is separation process using hot water medium. The process was carried out in a stirred tank, 200 grams of asbuton was mixed with diesel oil and added by hot chemical solution (surfactant) in the digestion tank. The separation process in the extractor was made at 900C and time set was 30 minutes. Surfactan concentration and the speed of stirrer were set according to the variable. After the process completed, the mixture was moved into a beaker glass and 500 ml hot water was added. The mixture of diesel oil and bitumen will float in the surface then the density will be measured to determine the bitumen concentration. It can be concluded that concentration of surfactant solution and speed of stirrer have the significant results. The highest recovery percentage of bitumen is 81,99 %. Keywords: Asbuton, Hot water, Speed of stirrer, Surfactant.